Impact of a simulated stress training program on the tactical shooting performance of SWAT trainees - Liu, Y.; Mao, L.; Zhao, Y.; Huang, Y. (Research Quarterly for Exercise and Sport, 2018)
Purpose: To create a high-stress shooting among the crowd (SAC) program and to examine its effectiveness in reducing SWAT trainees' stress level and their shooting performance in a simulated hostage-rescue situation. Method: After the SAC program was created, it was evaluated using a pretest and posttest experimental design: 98 young male SWAT trainees were randomly divided into experiment and control groups, with the former group trained in hostage rescue, shooting with real persons (high stress), and the latter group trained with "dummy" men (low stress); training for both lasted three days. Their shooting performance was assessed by a tactical shooting test in both high- and low-stress tests in a counterbalanced order, before and after the training, and monitored during the training, as were their stress levels by a set of physical (heart rate [HR] and heart rate recovery time [HRRt]), psychological (salivary cortisol and alpha-amylase), and self-reported anxiety measures. Results: The SAC program created needed high-stress for hostage rescue situations as reflected in increased physical, psychological, and anxiety scores and reduced shooting performance. Even with short SAC training, SWAT trainees' capacity in handling high stress and tactical shooting performance were significantly improved. HR, HRRt, and anxiety tests have been found to be effective in monitoring stress and should be a part of future SWAT training. Conclusion: A SAC program involving real people was created, and its effectiveness was confirmed using a pretest and posttest experimental design.